Law And Ethics In The Malaysian Insurance Industry: A Review Of Selected Practices - Chew Li Hua, Nurjaanah Abdullah (Journal of Malaysian and Comparative Law, 2004)
The insurance industry, especially insurers, is one of the most regulated commercial entities. This is due to its unique role and impact on society. The very nature of its business is sui generis as insurance is in a class of its own. Thus, although it is a profit motivated industry like any other business, the health of the industry is determined to a certain extent by the ethical practices or lack of them in the daily running of the industry. What has ethics to do with the insurance industry? This article explores the co-relations between the law, ethics and practice in the insurance industry. The doctrine of ubberimae fidei and the principle of indemnity set a contract of insurance apart from other types of commercial contracts. Several examples of insurance industry practices which may fulfill the legal principles and requirements but may be ethically suspect will be discussed. These are practices in the formation of contract, the practices of insurance agents, the practice of inserting unfair terms in the form of the basis of contract clause and limiting the time frame to submit a claim, the practice of avoiding claims on the basis of absence of insurable interest, and the practice of prolonging delays unreasonably in the settling of claims.